Keterlibatan Orangtua dan Masyarakat Dalam Pendidikan Anak Usia Dini - Dwi Bhakti Indri M (Program Studi PGMI STAI Daruttaqwa Gresik, 2020)
There is the term parental involvement, which not only refers to biological parents but also refers to people who take care of children. For example, grandparents, aunts, or others. In other words, the parent in question is someone who provides care for the child in question. Parental participation in educating children is a form of parental participation that shows commitment, dedication, and involvement of parents in children's education. In addition, community participation cannot be separated from the educational development of a child. In other words, the role and involvement of parents and society have a close relationship with individual education.